Impact of Co-Administration of N-Acetylcysteine and Vitamin E on Cyclophosphamide-Induced Ovarian Toxicity in Female Rats - Mahdieh Raeeszadeh; Seed Mohammad Saleh Hosseini; Ali Akbar Amiri (Journal of Toxicology)
Cyclophosphamide is used to treat various types of cancer. However, it can reduce ovarian function and fertility rate. The current study was done to compare the effects of N-acetylcysteine and vitamin E on cyclophosphamide-induced ovarian damage. Thirty-five rats were randomly divided into 5 groups: control (C), cyclophosphamide (CP, 200 mg/kg single dose intraperitoneally), T1 (cyclophosphamide + vitamin E at 200 mg/kg), T2 (cyclophosphamide + 200 mg/kg N-acetylcysteine), and T3 (cyclophosphamide + N-acetylcysteine and vitamin E at 200 mg/kg). The main measurements included total antioxidant capacity (TAC), glutathione peroxidase (GPx), malondialdehyde (MDA), interleukin 8 (IL-8), tumor necrosis factor-α (TNFα), follicle stimulating hormone (FSH), luteinizing hormone (LH), and estrogen (ES). Except for the C and T3 groups, the other groups lost weight. A significantly lower concentration of MDA was observed in the T3 group. However, TAC was substantially increased compared to the other groups. The level of GPx in the S group was significantly reduced compared to all groups. Proinflammatory markers (IL-8 and TNFα) reached their lowest serum level in the T3 group, with a statistically significant difference compared to that of the S group. In addition, there were no significant differences in the means of primary, secondary, and graph and atretic follicles between the T3 and C group. On the other hand, a decrease in FSH and LH was observed while an increase in ES was seen in the T3 group compared to the S group. This study revealed that N-acetylcysteine and vitamin E coadministration could significantly decrease the side effects of cyclophosphamide, especially in ovarian tissue.